Inside Back Cover: Volume 1 Issue 2. Issue 2 (30th April 2022) - Unknown
Abstract : Inside Back Cover : Artificial nanomotors have nanoscale sizes and are capable of autonomously moving with taxis by harvesting local energy. They may actively enter the tissues and cells of lesion locations, and thus revolutionize the diagnosis and treatment of diseases.